Persist and cope: New Zealand women in computing - Alison Hunter (Journal of Applied Computing and Information Technology)
New Zealand has a thriving computing industry but further growth is hampered by a skills shortage. A lack of women in the industry exacerbates this problem. Women are under-represented in the industry, and those who do take up computing careers experience conditions of discrimination and marginalisation. This paper reports on a qualitative study of the strategies used by women to cope with their marginalisation. Using multi-sited ethnographic methodology, data were collected using semi-structured interviews with twenty-nine computing professionals. Despite some women denying any marginalisation, all were found to employ some form of coping strategy. Seven different strategies were identified. The women interviewed were more inclined to join organisations directly relating to their roles rather than support initiatives which might improve conditions for women.